Cultural security in the perinatal period for Indigenous women in urban areas: a scoping review. Issue 5 (October 2019) - Marriott, Rhonda; Strobel, Natalie A.; Kendall, Sally; Bowen, Angela; Eades, Anne-Marie; Landes, Jasmin K.; Adams, Claire; Reibel, Tracy
Abstract: Background: Culturally secure care is considered foundational for good perinatal outcomes for Indigenous women. It is unknown what literature reports on whether Indigenous women giving birth in urban areas receives appropriate cultural care. The aim of this scoping review was to examine and summarise relevant evidence which reports on culturally secure care for Indigenous women using urban maternity services at any time during the perinatal period. Methods: Ten journal databases plus grey literature and theses databases were searched for relevant material dated 1986-2018. Articles were included if they were about Indigenous women from Australia, New Zealand, Canada or the USA; care was provided anytime during the perinatal period, in an urban area; and cultural security (or variations of this term) were used. Results: 6856 titles and abstracts were screened, of these: 25 studies, 15 grey literature documents and 9 theses matched the search criteria. Studies were mostly qualitative (13/25) and from Australia (18/25). Studies showed women's access to and experiences of culturally secure maternity care in urban areas as variable. The grey literature originated from Australia (8/15); New Zealand (4/15); and Canada (3/15); while theses were from Canada (7/9) and Australia (2/9). Conclusion: The scoping review results showed substantial qualitative evidence on Indigenous women's experience during the perinatal period in urban areas. In-depth analysis of these studies is required to inform future practice and policy on what works and what needs improvement. Culturally secure midwifery care shows promising results.